2007
DOI: 10.1111/j.1365-2672.2007.03553.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of agricultural residues for poly(3-hydroxybutyrate) production by Halomonas boliviensis LC1

Abstract: Aims:  Utilization of cheap and readily available agricultural residues as cheap carbon sources for poly(3‐hydroxybutyrate) (PHB) production by Halomonas boliviensis. Methods and Results:  Wheat bran was hydrolysed by a crude enzyme preparation from Aspergillus oryzae NM1 to provide a mixture of reducing sugars composed mainly of glucose, mannose, xylose and arabinose. Growth of H. boliviensis using a mixture of glucose (0·75% w/v) and xylose (0·25% w/v) in the medium led to a PHB content and concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
3
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 35 publications
4
74
3
3
Order By: Relevance
“…This could be attributed to these substrates being rich in protein, or other nutrients as well that triggered the growth phase instead of nutrient depletion. Similar observations were made by Van-Thuoc et al (2007) and Ramadas et al (2009) wherein wheat bran and cassava bagasse supported good growth but low PHB accumulation. There was a positive correlation between the amount of reducing sugar released [data not shown] by acid hydrolysis of the substrates with the PHB yield obtained (r = 0.70538).…”
Section: Evaluation Of Agro-industrial Residues As Carbon Substratesupporting
confidence: 73%
See 1 more Smart Citation
“…This could be attributed to these substrates being rich in protein, or other nutrients as well that triggered the growth phase instead of nutrient depletion. Similar observations were made by Van-Thuoc et al (2007) and Ramadas et al (2009) wherein wheat bran and cassava bagasse supported good growth but low PHB accumulation. There was a positive correlation between the amount of reducing sugar released [data not shown] by acid hydrolysis of the substrates with the PHB yield obtained (r = 0.70538).…”
Section: Evaluation Of Agro-industrial Residues As Carbon Substratesupporting
confidence: 73%
“…However, 4 g/L PHB has been obtained from R. eutropha using hydrolyzed starch. Van-Thuoc et al (2007) reported that in order to use the agroindustrial residues as fermentation substrates, these should be subjected to hydrolysis for the release of easily metabolizable sugars. Acid and enzymatic methods are the two main reported methods for the hydrolysis, but acid hydrolysis requires more energy for heating and is relatively difficult to control.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Halomonas is well known for being able to synthetize PHA, many species in this family assimilate several different carbon sources that can be obtained from waste residues or by-products and has the potential to be used as inexpensive raw materials for PHA production [20]. According to [21] Halomonas boliviensis has been already reported to produce polyhydroxyalkanoates from several different carbon sources, like glucose, xylose, sucrose, maltooligosacharides, sodium acetate and butyric acid. Currently alternatives ways for improving PHA production are being investigated by other researchers with representatives of genus Halomonas by using less expensive substrates and scaling-up fermentation.…”
Section: Discussionmentioning
confidence: 99%
“…A wide range of industrial by-products has been used for PHAs production like agricultural, household waste materials, sugars, lignocellulosic raw materials, fats, and oils. Among those, extensive research is focused on wastes, sucrose [108], starch [109], glucose [110][111][112], soy molasses and hydrolysed soy [113,114], sugar cane molasses [115][116][117], waste rapeseed oil [118,119], sunflower meal hydrolysates [120], glycerol [121,122], rice bran and corn starch [74], lard oil, butter oil, and coconut oil [123], palm oil and its products [124], sugar beet molasses [125], spent palm oil [126], cellulose and cellulose hydrolysates [127], sugarcane bagasse hydrolysates [128,129], casein hydrolysate [130], rapeseed meal hydrolysates [131], triacylglycerides (TAG) [132], sugarcane liquor [133], acetic acid [111,134], corn steep liquor [135], fish peptone medium [136], galactose, mannose and rhamnose [137], cheese whey and hydrolysed whey [115,138,139], urea [117], oil [124], wheat based biorefinery [140,141], xylose [128], arabinose …”
Section: Selection Of Feedstocksmentioning
confidence: 99%